2021
DOI: 10.1063/5.0071911
|View full text |Cite
|
Sign up to set email alerts
|

X-ray-induced acoustic computed tomography (XACT) imaging with single-shot nanosecond x-ray

Abstract: X-ray-induced acoustic computed tomography (XACT) has emerged as a promising imaging modality with broad applications in both biomedicine and nondestructive testing. The previous XACT imaging systems require thousands of averages to achieve reasonable images. Here, we report the experimental demonstration of single-shot XACT imaging of a metal object using a single-shot 50 ns x-ray pulse. A two-stage dedicated amplification and a 128-channel parallel data acquisition configuration were introduced for XACT imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…However, there will be challenges for the strong attenuation of higher frequency ultrasound signals in large size human bone. (2) XACT imaging may be a lower dose diagnostic imaging technique as compared to the current CT imaging because of 3D image can be obtained with single X‐ray projection 62 . Recent publication shows that the minimal X‐ray dose for imaging a 100‐μm calcification with XACT is about 0.36 mGy 44 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there will be challenges for the strong attenuation of higher frequency ultrasound signals in large size human bone. (2) XACT imaging may be a lower dose diagnostic imaging technique as compared to the current CT imaging because of 3D image can be obtained with single X‐ray projection 62 . Recent publication shows that the minimal X‐ray dose for imaging a 100‐μm calcification with XACT is about 0.36 mGy 44 .…”
Section: Discussionmentioning
confidence: 99%
“…(2) XACT imaging may be a lower dose diagnostic imaging technique as compared to the current CT imaging because of 3D image can be obtained with single X-ray projection. 62 Recent publication shows that the minimal X-ray dose for imaging a 100-µm calcification with XACT is about 0.36 mGy. 44 Our recent publication has further demonstrated that XACT images can be performed with just a single-shot X-ray pulse in 50 ns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently FLASH mode therapy is only used in research; however, its characteristics may be beneficial in solidifying XACT as a dosimetric tool: a higher dose per pulse can considerably increase the SNR, and the spatial resolution limited by the 4 μs of conventional therapy can be overcome. Another recent study reported the experimental demonstration of XACT of a metallic object using single-pulses of 50 ns, exhibiting the growing benefits of these ultrafast radiation pulses 26 .…”
Section: Discussionmentioning
confidence: 99%